From child welfare to jail: mediating effects of juvenile justice placement and other system involvement - Goodkind, Sara (Child maltreatment, 2020)
This study examines the effects of child welfare, mental health, and drug/alcohol system experiences on jail involvement, as mediated by juvenile justice placement, for Black and White youth/young adults. The sample was comprised of individuals born between 1985 and 1994 with child welfare involvement in an urban Pennsylvania county (N = 37,079) and an out-of-home placement (OOHP) subsample (n = 8,317). Four path models were estimated (two full samples, two subsamples; separate models for Black and White youth). For all models, juvenile justice placement was positively related to jail involvement. For the full samples, out-of-home child welfare placement was associated with an increase in juvenile justice placement. Within the Black placement sample, child welfare placement experiences had complex relationships with juvenile justice placement. Providing drug/alcohol services may be a protective factor for Black youth prior to juvenile justice contact. Articulating these relationships helps identify youth most at risk of justice system involvement and better targets services, especially mental health and drug/alcohol services.